การสำรวจอะแคนทามีบาในตัวอย่างน้ำสวนสาธารณะในประเทศไทย - Buppan, Pattakorn; Meeboon, Chalalai; Klamsiri, Thitinan; Promyuttana, Warakorn; Ko-amornsup, Wasumadee; Kosuwin, Rattiporn; Srimee, Pakarang (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2018)
Survey of Acanthamoeba spp. in Water Samples from the Public Park of Thailand Pattakorn Buppan, Chalalai meeboon, Thitinan Klamsiri, Warakorn Promyuttana, Wasumadee Ko-amornsup, Rattiporn Kosuwin and Pakarang Srimee รับบทความ: 14 กันยายน 2560; ยอมรับตีพิมพ์: 29 มีนาคม 2561 บทคัดย่อ อะแคนทามีบาเป็นอะมีบาที่ดำรงชีวิตเป็นอิสระในสิ่งแวดล้อมและเป็นเชื้อฉวยโอกาสที่ทำให้เกิดโรคสมองอักเสบชนิดเรื้อรัง โรคผิวหนังชนิดเฉียบพลัน และโรคกระจกตาอักเสบ การศึกษานี้มีวัตถุประสงค์เพื่อสำรวจความชุกของอะแคนทามีบาจากตัวอย่างน้ำที่เก็บสวนสาธารณะและจัดกลุ่ม อะแคนทามีบาโดยใช้รูปร่างลักษณะของซีสต์ จากตัวอย่างน้ำทั้งหมด 300 ตัวอย่างที่อุณหภูมิเฉลี่ย 24.53 องศาเซสเซียส ค่า pH ประมาณ 5.3 โดยเพาะเลี้ยงอะแคนทามีบาบนอาหารเลี้ยงเชื้อที่ฉาบด้วย Escherichia coli ผลการวิจัยพบ Acanthamoeba spp. ร้อยละ 35 ของจำนวนตัวอย่างทั้งหมด จังหวัดสระบุรีและสงขลาพบความชุก Acanthamoeba spp. มากที่สุด และจังหวัดนครราชสีมาและราชบุรีพบความชุกของ Acanthamoeba spp. น้อยที่สุด โดยสามารถแบ่งเป็นลักษณะซีสต์ที่พบได้ 3 กลุ่ม และลักษณะซีสต์กลุ่มที่ 2 พบจำนวนมากที่สุด จากการศึกษานี้แสดงให้เห็นว่าอะแคนทามีบาสามารถพบได้ตามแหล่งน้ำสวนสาธารณะซึ่งเป็นข้อมูลที่จำเป็นเพื่อเฝ้าระวังการติดเชื้ออะแคนทามีบา คำสำคัญ: อะแคนทามีบา สวนสาธารณะ อะมีบาดำรงชีพอิสระ Abstract Acanthamoeba are free-living amoebae found in the environment and are opportunistic pathogens causing infections of the Granulomatous Amebic Encephalitis (GAE), Acanthamoeba Keratitis (AK) and Subacute granulomatousn dermatitis. The aim of this study was to investigate the prevalence of Acanthamoeba spp. in water samples from the public park and identify Acanthamoeba spp. based on the morphology of cyst. A total of 300 water samples were recovered at average of 24.53°C, approximate pH 5.3. The Acanthamoeba spp. were cultured in non-nutrient agar coated with Escherichia coli and observed the morphology under compound light microscope. The results showed that there were 35% of Acanthamoeba spp. from total water samples. The highest prevalence of Acanthamoeba spp. was found in Saraburi and Songkhla, whereas the lowest prevalence was found in Nakhon Ratchasima and Rat-chaburi. Acanthamoeba spp. in this study were classified into 3 groups based on cyst morphology, and the highest prevalence of cyst were classified in group II. This study suggested that Acanthamoeba spp. can be found the water samples collected from the public park. It is es-sential information to monitor the Acanthamoeba spp. infection. Keywords: Acanthamoeba spp., Public park, Free-living amoebae (FLA)